1973
DOI: 10.1677/joe.0.0570253
|View full text |Cite
|
Sign up to set email alerts
|

The Lactogenic Effects of Prolactin and Growth Hormone on Mammary Gland Explants From Virgin and Pregnant Sprague-Dawley Rats

Abstract: Explants of mammary glands from mature virgin and pregnant Sprague\p=m-\ Dawley rats were maintained in organ culture for up to 96 h. The effects of insulin, corticosterone, ovine prolactin and bovine growth hormone on the synthesis of DNA, RNA and casein in the explants were studied. DNA synthesis in explants from virgin rats was maintained by insulin but was not increased by the addition of the other hormones tested. DNA synthesis in explants from pregnant rats was increased by insulin, and the addition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1977
1977
1987
1987

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…They observed no response at 10~9 M prolactin (about 20 ng/ml), but a maximal response at the next highest concentration tested, 10-8 M (about 200 ng/ml). These results are in contrast to those of Turkington [ 17] using cultured mouse tissues and Hallowes et al [ 18] using cultured rat tissues; these authors observed maximal rates of [32P] incorporation into casein with prolactin concentrations as high as 0.5-5 pg/ml. Since the experiments of Stockdale et al [16], Turkingion [17] and Hallowes et al [18] were all carried out with (a) prolactin present in the culture medium for 48 h and (b) prolactin present from the time of preparation of the explants, it seems possible that hormone degradation during culture may explain why these authors had to use such high concentrations of prolactin to obtain maximal effects on casein synthesis.…”
Section: Discussioncontrasting
confidence: 88%
“…They observed no response at 10~9 M prolactin (about 20 ng/ml), but a maximal response at the next highest concentration tested, 10-8 M (about 200 ng/ml). These results are in contrast to those of Turkington [ 17] using cultured mouse tissues and Hallowes et al [ 18] using cultured rat tissues; these authors observed maximal rates of [32P] incorporation into casein with prolactin concentrations as high as 0.5-5 pg/ml. Since the experiments of Stockdale et al [16], Turkingion [17] and Hallowes et al [18] were all carried out with (a) prolactin present in the culture medium for 48 h and (b) prolactin present from the time of preparation of the explants, it seems possible that hormone degradation during culture may explain why these authors had to use such high concentrations of prolactin to obtain maximal effects on casein synthesis.…”
Section: Discussioncontrasting
confidence: 88%
“…Rabbit antimouse casein (5) and rat and mouse caseins were gifts from Dr. M. Feldman (Children's Hospital Medical Center, Oakland, Calif.) and Dr. S. Young (I. C. R. F., London, England), respectively. The antiserum was absorbed with mouse serum and stored with 0.01% methiolate in phosphate-buffered saline, while the caseins were prepared from milk by precipitation with renin (11,39). Cell culture media, medium 199, Dulbecco's modified Eagle's medium (DEM), and Waymouth's medium (24) were supplied by the I. C. R. F., fetal calf serum was purchased from Gibco-Biocult (Glasgow, Scotland).…”
Section: Methodsmentioning
confidence: 99%
“…PRIMARY CULTURES: After a total of 67 h of incubation, 1 ~tCi/ml of [aH]thymidine at 1 ~tM was added to the cultures. 2 h later, the cultures were washed and the uptake of [SH]thymidine incorporated into DNA (aH-cpm/#g of DNA) was determined as before (11,17). Results given are the mean of three separate dishes -+ the standard error.…”
Section: Estimation Of Dna Synthesis and Cell Divisionmentioning
confidence: 99%
“…In mice, Mayne & Barry (1970) and Oka & Topper (1972) found no stimulatory effect of prolactin on DNA synthesis by organ cultures of mammary gland, whereas Mukherjee et al (1973) have provided evidence to the contrary. In rats, Dilley (1971) and Hallowes et al (1973) have reported that prolactin is mitogenic in vitro to the mammary epithelium, whereas Koyama et al (1972) did not see any stimulatory effect of prolactin on mammary-gland growth in vitro.…”
mentioning
confidence: 99%